2019
DOI: 10.1177/1049732319880551
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Health Experience and Action through Shifting the Narrative on Obesity in Primary Care Encounters

Abstract: We sought to understand the impact of primary care conversations about obesity on people’s everyday life health experience and practices. Using a dialogic narrative perspective, we examined key moments in three very different clinical encounters, the patients’ journals, and follow-up interviews over several weeks. We trace how people living with obesity negotiate narrative alternatives that are offered during clinical dialogue to transform their own narrative and experience of obesity and self. Findings provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Rather PWO tended to feel lifestyle factors were most important, which matches similar survey studies (Grannell et al, 2020;Kaplan et al, 2018). Luig et al (2020) examined how PWO in primary care settings respond to alternative narratives regarding obesity. They found that PWO initially portrayed self-depreciating narratives about their disease.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Rather PWO tended to feel lifestyle factors were most important, which matches similar survey studies (Grannell et al, 2020;Kaplan et al, 2018). Luig et al (2020) examined how PWO in primary care settings respond to alternative narratives regarding obesity. They found that PWO initially portrayed self-depreciating narratives about their disease.…”
Section: Discussionmentioning
confidence: 60%
“…PWO appear to have an incomplete understanding regarding obesity as a disease which is characterized by appetite dysregulation promoting both unintentional weight gain and regain after weight loss. Given the complexity of obesity, it is unsurprising the participants gave diverse perspectives with Luig et al (2020) similarly detailing that PWO feel their disease is a puzzling experience. There is a need to educate all key stakeholders regarding the biology of the disease and push toward a better understanding of obesity as a disease.…”
Section: Discussionmentioning
confidence: 99%
“…Clinicians should be proactive in screening, not wait for clients to initiate conversations about these issues. While this is acknowledged as highly challenging for clinicians, novel research may offer ideas for delivering patient-centered care, such as emphasizing a self-compassionate stance during clinical consultations (Luig et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…From my personal interviews with my colleague family physicians, neurologists and pain management specialists, nutritional counseling in their clinics go as far as a five to ten minute talk to patients about Dietary Approaches to Stop Hypertension (DASH) or Mediterranean diet and their recommendation to the patients to lose weight without further guidance or referral. Based on these interviews and a literature search for research evidence in this area, this indicates the need to increase referral to nutritionists and dietitians among obese patients with ASD [17]. Another important element that has been lacking and overlooked in the care of these patients is psychological evaluation and therapy throughout their care, not just a one-time routine presurgical psychological evaluation.…”
Section: Opinionmentioning
confidence: 99%